Creditor rights and innovation: Evidence from patent collateral - Mann, William (Journal of Financial Economics, 2018)
I show that patents are pledged as collateral to raise significant debt financing, and that the pledgeability of patents contributes to the financing of innovation. In 2013, 38% of US patenting firms had previously pledged patents as collateral, and these firms performed 20% of research and development expense and patenting in Compustat. Employing court decisions as a source of exogenous variation in creditor rights, I show that patenting companies raised more debt, and spent more on R&D, when creditor rights to patents strengthened. Subsequently, these companies exhibited a gradual increase in patenting output and the use of patents as collateral.